Novel Gels for Post-Piercing Care: Evaluating the Efficacy of Pranoprofen Formulations in Reducing Inflammation - Negar Ahmadi; Maria Rincón; Mireia Mallandrich; Joaquim Suñer-Carbó; Lilian Sosa; Mireya Zelaya; Sergio Martinez-Ruiz; Cecilia Cordero; Ana C. Calpena (Gels)
Mild to moderate pain for a few hours to several days post-piercing is normal, and the pain is usually accompanied by swelling, redness, and warmth due to the inflammatory response. Cool compresses and over-the-counter analgesics (e.g., NSAIDs) can ease mild discomfort. However, oral NSAIDs may have systemic side effects; for this reason, we propose a topical anti-inflammatory approach. Four pranoprofen-loaded gels were created using different gelling agents: Sepigel® 305 (PF-Gel-Sep), Carbopol® 940 (PF-Gel-Car), Pluronic® F-68 (PF-Gel-Plu), and Lutrol® F-127 (PF-Gel-Lut). The gels were assessed for pH, morphology, FT-IR spectroscopy, rheological properties, spreadability, swelling and degradation, drug release kinetics, skin permeation (cow and human skin), irritation potential (HET-CAM assay), and impact on skin barrier function (TEWL and SCH). The gels exhibited varied rheological properties with PF-Gel-Car showing high viscosity and PF-Gel-Plu very low viscosity. All gels had similar spreadability with PF-Gel-Lut showing the highest. PF-Gel-Car showed the highest amounts of PF released, whereas PF-Gel-Plu led to the highest amount of pranoprofen retained in human and bovine skin. The HET-CAM assay indicated that none of the PF-Gels were irritating. Additionally, PF-Gel-Car and PF-Gel-Plu showed no cytotoxic effects on HaCaT cells. In vivo testing on mice showed that PF-Gel-Car prevented inflammation, while the rest of the gels were able to revert it in 25 min. Skin tolerance tests revealed the gels did not affect TEWL, and some gels improved SCH. The study successfully formulated and characterized four PF-loaded topical gels with potential to be used as an alternative for treating inflammation from piercings and ear tags.